French il y a clefts, existential sentences and the Focus-Marking Hypothesis - KARSSENBERG, LENA (Journal of French language studies, 2017)
This article presents the results of a corpus analysis of the information structure properties of il y a clefts (e.g. Il y a Claude qui chante ‘There is Claude who is singing’ / ‘Claude is singing’). I will show that il y a clefts and existential sentences introduced by il y a can express the same three information structure articulations. Furthermore, it will be argued that il y a clefts and existential sentences function as focus markers, and that this hypothesis is further supported by psycholinguistic findings concerning constructions related to il y a.